Effectiveness of integrated learning for promoting holistic development elementary students: Systematic review and meta-analysis - I Bagus Endrawan; Winara Winara; Ahmad Yani; Alficandra Alficandra; Martinus Martinus; Kamarudin Kamarudin; Balkis Ratu NL Esser; Jujur Gumilar Manullang (Journal of Physical Education (Maringá), 2025)
This study aimed to identify implementation strategies and evaluate their effectiveness in enhancing student engagement and skill acquisition. Five studies were selected through a systematic literature review and meta-analysis from Scopus and Web of Science databases, applying strict inclusion criteria. These studies employed diverse integrative learning approaches to Physical Education (PE), including curriculum-embedded physical activity (PA), game-based learning, and structured physical literacy programs. The aggregated effect size favored the experimental groups, which indicated a standardized mean difference (SMD) of 0.91 (95% CI: -0.45 to 2.28; p = 0.19). Nevertheless, the analysis demonstrated a high level of heterogeneity (I² = 99%), indicating that variations substantially influence outcomes in population characteristics, implementation fidelity, and intervention type. The generalizability of the findings is limited by several studies and substantial variability, even though most interventions yielded positive trends. Integrative learning in PE has the potential to enhance physical engagement, knowledge acquisition, and psychosocial development in primary education, as this review emphasizes. However, additional investigations are required. Future research should evaluate integrative PE's long-term sustainability and viability across diverse educational settings, investigate moderators such as cultural context, program duration, and learner diversity, and embrace standardized designs.